Cholesteryl Ester Transfer Protein Inhibition With Anacetrapib Decreases Fractional Clearance Rates of High-Density Lipoprotein Apolipoprotein A-I and Plasma Cholesteryl Ester Transfer Protein. Issue 5 (May 2016) - Reyes-Soffer, Gissette; Millar, John S.; Ngai, Colleen; Jumes, Patricia; Coromilas, Ellie; Asztalos, Bela; Johnson-Levonas, Amy O.; Wagner, John A.; Donovan, Daniel S.; Karmally, Wahida; Ramakrishnan, Rajasekhar; Holleran, Stephen; et al.
Abstract : Objective—: Anacetrapib (ANA), an inhibitor of cholesteryl ester transfer protein (CETP) activity, increases plasma concentrations of high-density lipoprotein cholesterol (HDL-C), apolipoprotein A-I (apoA)-I, apoA-II, and CETP. The mechanisms responsible for these treatment-related increases in apolipoproteins and plasma CETP are unknown. We performed a randomized, placebo (PBO)-controlled, double-blind, fixed-sequence study to examine the effects of ANA on the metabolism of HDL apoA-I and apoA-II and plasma CETP. Approach and Results—: Twenty-nine participants received atorvastatin (ATV) 20 mg/d plus PBO for 4 weeks, followed by ATV plus ANA 100 mg/d for 8 weeks (ATV-ANA). Ten participants received double PBO for 4 weeks followed by PBO plus ANA for 8 weeks (PBO-ANA). At the end of each treatment, we examined the kinetics of HDL apoA-I, HDL apoA-II, and plasma CETP after D3-leucine administration as well as 2D gel analysis of HDL subspecies. In the combined ATV-ANA and PBO-ANA groups, ANA treatment increased plasma HDL-C (63.0%; P <0.001) and apoA-I levels (29.5%; P <0.001). These increases were associated with reductions in HDL apoA-I fractional clearance rate (18.2%; P =0.002) without changes in production rate. Although the apoA-II levels increased by 12.6% ( P <0.001), we could not discern significant changes in either apoA-II fractional clearance rate or production rate. CETP levels increased 102% ( P <0.001) on ANA because of a significant reduction in the fractional clearance rate of CETP (57.6%, P <0.001) with no change in CETP production rate. Conclusions—: ANA treatment increases HDL apoA-I and CETP levels by decreasing the fractional clearance rate of each protein. Abstract : Supplemental Digital Content is available in the text.